Ultrashort-pulse laser ablation of silicon toward device applications - Hsu, Eugene (My University, 2012)
This thesis presents investigations on ultrafast laser irradiation of silicon towards the goal of hybridizing ultrafast laser processing and conventional semiconductor fabrication techniques to improve device applications. The fundamental sub-threshold damage accumulation mechanisms for potential defect engineering applications were studied through the use of positron annihilation spectroscopy, in situ sample heating during laser irradiation, varying the laser repetition rate, and samples implanted with various ion species at diﬀerent conditions. Positron annihilation spectroscopy results suggest an increase in the divacancy density at the surface region of silicon following near- and slightly sub-threshold ultrafast laser irradiations. Laser irradiations at increasing sample temperature up to 600°C show a general decreasing trend of single-shot thresholds, and an increase in the suppression of sub-threshold damage accumulation. There is also a temperature dependence on the surface morphology resulting from ultrafast laser irradiation. Ion implantation modiﬁed the ablation threshold ﬂuence, and a dependence on the ion implantation conditions was observed. Surface microstructuring of silicon was shown to improve absorption of light with a sub-bandgap wavelength of 1550 nm. An initial attempt with sulfur implantation did not exhibit further improvement in the optical absorption, and ﬁrst attempts in device fabrication did not provide photoresponsivity at sub-bandgap wavelengths. Ultrafast laser irradiation of SiO2-on-Si structures yielded diﬀerent modiﬁcation thresholds for diﬀerent thicknesses of the oxide layer. Surface morphologies obtained in the irradiation of these structures can aﬀect potential applications. Selected studies of ultrafast laser irradiation of GaP, metal-SiO2-Si structures, quartz, diamond, and porcine bone demonstrated similarities in ablation behavior and morphologies, and the potential for a broad range of applications. The results in combination with the proposed future work in this thesis can contribute to potential device applications while providing valuable insights into the ultrafast laser ablation mechanisms.
Keywords: Ultrafast laser micromachining; ablation; black silicon; Engineering Physics; Engineering Physics